The Puyehue-Cordón Caulle Volcanic Eruption, June 2011: Water Vapor, Atmospheric Boundary Layer and Aerosol Temporal Evolution in Buenos Aires, Argentina - Otero, Lidia Ana (2011)
The 4th June 2011 a volcano eruption in the Puyehue – Cordón Caulle chain in the south central region of Chile released an important amount of ash to the atmosphere. The cloud reached Argentina, Uruguay, Brazil, South Africa and Australia blocking the aerial transport. A multiwavelength backscatter Raman LIDAR, developed and operational in Buenos Aires, at Centro de Investigaciones en Láseres y Aplicaciones, CEILAP (CITEDEF-CONICET), (34.5° S, 58.5° W) observed this event as well as satellites and ground-based systems of this monitoring station. The source of this lidar is a tripled Nd:YAG laser, collecting the nitrogen Raman backscattered returns from nitrogen at visible and ultraviolet wavelengths to retrieve the aerosol extinction and Ångström coefficient vertical distribution. It also measures the water vapor mixing ratio profile at the corresponding Ramanshifted backscattered return. Additional information such as satellite imaging, backtrayectories (HYSPLIT model) and aerosol optical depth (AERONET) were included on this study.